2023
DOI: 10.1007/s12519-022-00671-w
|View full text |Cite
|
Sign up to set email alerts
|

Longer duration of initial invasive mechanical ventilation is still a crucial risk factor for moderate-to-severe bronchopulmonary dysplasia in very preterm infants: a multicentrer prospective study

Abstract: Objectives We aimed to evaluate the risk factors for moderate-to-severe bronchopulmonary dysplasia (BPD) and focus on discussing its relationship with the duration of initial invasive mechanical ventilation (IMV) in very preterm neonates less than 32 weeks of gestational age (GA). Methods We performed a prospective cohort study involving infants born at 23–31 weeks of GA who were admitted to 47 different neonatal intensive care unit (NICU) hospitals in Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A prospective multicenter cohort study included 6,538 infants born at 23–31 weeks of GA who were admitted to 47 NICUs in China from January 2018 to December 2021. It further revealed that the onset of moderate-to-severe BPD was significantly associated with the duration of initial invasive MV (adjusted OR 1.97; 95% CI 1.10–2.67) 26 . For severe BPD, a single-center, retrospective cohort study included infants born at 22.0–25.9 weeks during 2005–2009 (88 infants in the early era) and 2011–2015 (102 infants in the late era), which was before and after implementing guidelines recommending delayed extubation.…”
Section: Discussionmentioning
confidence: 94%
“…A prospective multicenter cohort study included 6,538 infants born at 23–31 weeks of GA who were admitted to 47 NICUs in China from January 2018 to December 2021. It further revealed that the onset of moderate-to-severe BPD was significantly associated with the duration of initial invasive MV (adjusted OR 1.97; 95% CI 1.10–2.67) 26 . For severe BPD, a single-center, retrospective cohort study included infants born at 22.0–25.9 weeks during 2005–2009 (88 infants in the early era) and 2011–2015 (102 infants in the late era), which was before and after implementing guidelines recommending delayed extubation.…”
Section: Discussionmentioning
confidence: 94%
“…Prolonged duration of ventilation remains a significant factor in severe BPD. A multicenter study reported that the median duration of mechanical ventilation in moderate-to-severe BPD was 26 days whereas the mild BPD group had a median duration of only six days [23]. Lapcharoensap et al, in their study, reported that patients with BPD have a high length of hospitalization compared to those without BPD (103 days vs. 66.5 days) [24].…”
Section: Discussionmentioning
confidence: 98%
“…Mechanical interventions are the mainstay for treating respiratory problems in preterm infants (49)(50)(51). However, recent studies have shown that mechanical ventilation and ventilator-induced lung injury (VILI) are critical risk factors for developing BPD (52).…”
Section: Discussionmentioning
confidence: 99%